2017
DOI: 10.1016/j.bbmt.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood Transplantation without Antithymocyte Globulin Results in Similar Survival but Better Quality of Life Compared with Unrelated Peripheral Blood Stem Cell Transplantation for the Treatment of Acute Leukemia—A Retrospective Study in China

Abstract: Although previous studies have demonstrated improved outcomes in umbilical cord blood transplantation (UCBT) by omitting antithymocyte globulin (ATG) in the conditioning regimen, this approach has not been comparatively studied in unrelated peripheral blood stem cell transplantation (UPBSCT). To compare the risks and benefits between UCBT without ATG and UPBSCT in patients with acute leukemia (AL), we conducted a multicenter retrospective study of 79 patients who underwent UCBT (myeloablative conditioning with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…In a previous study, we found that MAC significantly improved the engraftment rate and OS and avoided an increase in NRM. In addition, prophylaxis of GVHD without using ATG showed remarkably increased engraftment rates for both neutrophils and platelets in CBT among children with acute leukemia [11, 19]. In the present study, we found that MAC without ATG for GVHD prophylaxis showed similar cumulative incidence of neutrophil engraftment of CBT in both AYAs and children; however, there was still a difference in the recovery rate of neutrophils between these patient populations.…”
Section: Discussionsupporting
confidence: 47%
“…In a previous study, we found that MAC significantly improved the engraftment rate and OS and avoided an increase in NRM. In addition, prophylaxis of GVHD without using ATG showed remarkably increased engraftment rates for both neutrophils and platelets in CBT among children with acute leukemia [11, 19]. In the present study, we found that MAC without ATG for GVHD prophylaxis showed similar cumulative incidence of neutrophil engraftment of CBT in both AYAs and children; however, there was still a difference in the recovery rate of neutrophils between these patient populations.…”
Section: Discussionsupporting
confidence: 47%
“…In addition, the timing, dose of ATG administration, and serum level at the time of the allograft infusion may influence incidence and grade of GVHD and T cell subset reconstitution [68,69]. In the absence of exposure to ATG, better T cell reconstitution after UCBT is observed, which may contribute, at least in part, to better leukemia control and lower all-cause mortality [68,70,71].…”
Section: Clinical Factors Associated With Immune Reconstitution Inmentioning
confidence: 99%
“…After using this protocol, we increased the UCBT engraftment rate; in addition, the infection rate, transplantation-related mortality, and relapse rate were decreased, while the incidence of acute GVHD (aGVHD) and chronic GVHD (cGVHD) did not increase [8]. In a multicenter study in China, we observed similar survival when comparing UCBT without ATG and unrelated peripheral blood stem cell transplantation (UPBSCT) but better quality of life in patients undergoing UCBT without ATG [9]. Therefore, we chose UCBT to treat patients with acute leukemia when an HLA-matched sibling donor was not available.…”
Section: Introductionmentioning
confidence: 83%